2022
DOI: 10.1097/ncc.0000000000001098
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Health-Related Quality of Life of Cancer Survivors According to Metabolic Syndrome

Abstract: Health-related quality of life Metabolic syndrome Background: Cancer survivors face an increased risk of non-cancer-related deaths, particularly associated with metabolic syndrome. With increased cancer survivors having metabolic syndrome, health-related quality of life beyond cancer diagnosis and treatment has assumed greater importance. Objective: This study evaluated the prevalence rate of metabolic syndrome in cancer survivors. It examined the correlation between healthrelated quality of life and influenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…An Italian randomized controlled trial found that an MD-based dietary intervention in g BRCA1/2 mutation carriers improved adherence to MD and reduced components of MetS [ 80 ]. Recent studies suggest that MetS is associated with impaired HRQoL [ 81 , 82 , 83 ]. Cohen et al [ 84 ] reported a positive association between pessimism and the prevalence of MetS in patients with coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…An Italian randomized controlled trial found that an MD-based dietary intervention in g BRCA1/2 mutation carriers improved adherence to MD and reduced components of MetS [ 80 ]. Recent studies suggest that MetS is associated with impaired HRQoL [ 81 , 82 , 83 ]. Cohen et al [ 84 ] reported a positive association between pessimism and the prevalence of MetS in patients with coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%